Implementasi Spline Interpolating Untuk Resampling Citra USG - Nasution, Rizky Saptiansyah (Bulletin of Data Science, 2023)
Spline interpolation is a form of interpolation in which the interpolation is a special type of spline polynomial. It's like attaching a single degree polynomial to all values ​​at once, then fitting a low degree polynomial to a small subset of values, for example fitting 9 cubic polynomials between each pair of ten points like a single ten degree polynomial for all of them. Comparisons were made in terms of gala and computational time. The process of calculating the error resulting from the absolute value of the value minus the approximation in the actual part multiplied by one hundred percent. The length of time indicated by the amount of data sought in the calculation process. After the resampling process on the image pixels is complete, the Red, Green and Blue images are re-united to get the RGB USG image back, the image will change in size, due to the addition of new pixels. If the initial image is 128x128, the new image will be 255x255.